Dilemma in Parkinson's Treatment; Levodopa Monotherapy May be the Best Choice. (September 2020) - Abbasi, Mohammad Hossein; Esmaeili, Sara; Habibi, Seyed Amirhassan; Shahidi, Gholam Ali
Highlights: Levodopa-Pramipexole combined therapy was associated with more severity of Parkinson. Psychotic side effects were more prevalent in receivers of Levodopa-Pramipexole combined therapy. Levodopa-Pramipexole combined therapy was associated with Lower HRQoL. Levodopa Monotherapy still offers more benefits and less side effects in PD. Abstract: Introduction: Several treatment strategies have been claimed for Parkinson's disease (PD) so far. However, there remains controversies over the best possible treatment. The aim of this study is to compare Levodopa monotherapy versus Pramipexole in combination with Levodopa L in patients with PD with regards to the efficacy and side effects. Methods: Patients being treated with levodopa alone and Pramipexole add-on therapy to Levodopa were enrolled in the study. Factors regarding efficacy and side effects were assessed and analyzed between both groups by appropriate tests. Results: 176 Patients were enrolled in the study. Results showed significant higher total MDS-UPDRS (worse total disease severity score) among patients being treated with Pramipexole add-on therapy which was particularly higher in parts 1 (Mentation, behavior and mood), 2 (Activity of daily living) and 3 (Motor examination) (P-values < 0.05). Psychosis global score with significantly higher frequency of hallucination and depression, statistically higher in combination therapy group compared to Levodopa monotherapy group (P-value < 0.05). Patients in the Pramipexole add-on group reported lower scores of Health-related quality of life (HRQoL) (P-value < 0.05). Significant correlation was between disease duration and psychosis score among Levodopa monotherapy group (P-value < 0.05). Conclusions: Compared to Levodopa monotherapy, Add-on therapy with Pramipexole shows less efficiency yet more side effects. This indicates that single administration of Levodopa still remains the best available treatment for Parkinson's disease.